Criteria and methodologies for determining the causes of swelling of canned tomatoes in tinplate containers. Issue 1 (5th December 2022) - Squitieri, Giuseppe; Pirone, Giuseppe; La Pietra, Liliana; Cannavacciuolo, Mariarosaria; Pezzani, Aldo; Ferrari, Giovanna; Castaldo, Domenico; Balestrieri, Maria Luisa; Cautela, Domenico
Abstract: This review provides the current laboratory criteria for the detection and evaluation of the possible causes of alteration of non‐concentrated industrial derivatives of tomatoes (peeled tomatoes, pulps, purees, sauces, and fillets), packaged in coated or uncoated tinplate cans. We discuss how the product alterations are typically the consequence of technological errors either in the can production, or in the storage process, or in the product sterilization. The described procedures include the quantitative determination of the distribution of gases (H2, CO2, N2, and O2 ) present in the headspace of the container. The gas composition and ratios can be used as markers to allow easy diagnosis of the causes of microbiologic and/or physical–chemical alterations of the tomatoes, which are usually made evident by swelling of the containers. These tests should be integrated by microbiological analyses aimed at a restricted group of microorganisms, with the chemical analysis of the container and the chemical analysis of the altered product. By way of example, we report the assessment of the causes of alteration in four different case‐studies.